Interactive and Digital Learning in The Third Decade of The Millenia: A Bibliometrics Analysis with Future Research - Siti Sharah Rajab; Nurahimah Mohd Yusoff; Muhammad Noor Abdul Aziz (Universitas Serambi Mekkah, 2024)
This paper explored a trend analysis related to interactive and digital learning from 1977 until July 2023. This research aimed to determine (1) the publication trends of interactive and digital learning; (2) the most prolific authors, themes, and topics; (3) the most institutions, countries, and highly cited documents of interactive and digital learning; (4) the essential keywords and themes involved in interactive and digital learning and (5) the pattern of co-authorship and topics from co-occurrence analyses of author keywords. The data were obtained through the Scopus database with the keywords “interactive learning” OR “digital learning.” The search resulted in 1161 documents. The data were exported and analyzed using tools such as BiblioMagica, BiblioMagika@Split, Microsoft Excel, VOSviewer, and Biblioshiny. The results showed that most publications were in 2021 and 2022. The most significant contributors with the most research documents were Lee, J. S. (14 publications), The Education University of Hong Kong by Institution (8.93%), English by Language (97.07%), United States by Country (21.19%), e-learning by trend topics with 217 frequencies. This study found the article “Seriously considering play: designing interactive learning environments based on the blending of microworlds, simulations and games” written by Rieber L. P. as the most cited publication. Moreover, five themes emerged based on the results of network visualization mapping, interactive and digital learning: (1) digital learning and technology, (2) technology in education, (3) adult learning and education, (4) learning technology and tools and (5) adapting education in the digital era. This study recommended a systematic literature review on popular topics such as e-learning and learning systems for further studies.